Legal Protection for Children Who Repeat Criminal Acts Through Special Child Development Institution (LPKA) - Ni Putu Ayu Mandalay Shasa Alba Chiara; Ni Made Jaya Senastri; Kade Richa Mulyawati (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
Children are the next generation of the nation, currently many criminal acts are committed by children. Guidance for children who commit crimes is carried out in LPKA. One of the current problems is the high number of cases of perpetrators who are former child convicts. The purpose of this study is to analyze the legal regulations related to criminal acts committed by children according to the SPPA Law, as well as to analyze legal protection for children who repeat criminal acts in LPKA. Legal regulations for children are included in lex specialis derogat legi generali, based on the SPPA Law which emphasizes diversion efforts if the sentence is under seven years and is not a repetition. Guidance for those who repeat criminal acts is not differentiated from the guidance of children who are new. Children who conflict with the law undergo guidance at LPKA, such as education, personality development, and independence development.